Development of Agile Supply Chains in Brazil - Mendes dos Reis, Joao Gilberto; Oliveira Costa Neto, Pedro Luiz de; Alves Fusco, Jose Paulo [UNESP]; Machado, Sivanilza Teixeira; Prabhu, V; Taisch, M.; Kiritsis, D. (Springer, 2013)
Agile supply chains or agile supply networks are those that adopt strategies for innovation and create customer/client needs before the customers/clients actually understand that they need such innovative products. Brazil is a developing country and belongs to the group of nations denominated BRICS, which, in addition to Brazil, involves Russia, India, China and South Africa. The purpose of this research was to study active companies in Brazil to verify the existence of agile companies in developing countries. First of all, this article applied the methodology to evaluated two companies considered agile in Brazil. Furthermore, this paper evaluated the scenario of the 100 largest companies in the country in the year 2012 (not included the two evaluated companies). The results show that among these companies, only one may be considered agile according to the methodology applied in this study.
Keywords: Agile Supply Chain; Supply Networks; Developing Countries; Brazil